2021
DOI: 10.17762/turcomat.v12i4.552
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Blended Learning Instruction: The Impact on Growing Motivation, Attitudes, and Knowledge in 3D Geometry

Abstract: The COVID 19 pandemic promotes several new technological products to facilitate learning process. However, there are still few studies on the integration of Augmented Reality (AR) technology into Blended Learning (BL), particularly on the education of prospective mathematics teachers. This research examines the effect of using augmented reality blended learning during the COVID 19 epidemic on 3D geometry, as well as the learning motivation and attitudes. 15 prospective teachers, including 4 males and 11 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…In a specific example, Radu, McCarthy, and Kao (2016) found that most Mathematics teachers in public schools in San Francisco expressed a general consensus that AR-based instructional tools can be beneficial in aiding students to visualize geometrical concepts such as 3D shapes and spatial properties. Furthe rmore, a study by Sudirman, Kusumah, and Martadiputra (2021) exploring teachers' perceptions of AR blended learning for advancing geometric knowledge further corroborated that teachers' view of the technology as pertinent to their instructional approach, helping them meet their students' learning objectives. Additionally, for instructors who had direct experience with technology and witnessed its benefits in teaching, they were also more inclined to integrate it into their curriculum for pupils (Cox & Graham, 2009;Kim & Lee, 2022).…”
Section: Introductionmentioning
confidence: 86%
“…In a specific example, Radu, McCarthy, and Kao (2016) found that most Mathematics teachers in public schools in San Francisco expressed a general consensus that AR-based instructional tools can be beneficial in aiding students to visualize geometrical concepts such as 3D shapes and spatial properties. Furthe rmore, a study by Sudirman, Kusumah, and Martadiputra (2021) exploring teachers' perceptions of AR blended learning for advancing geometric knowledge further corroborated that teachers' view of the technology as pertinent to their instructional approach, helping them meet their students' learning objectives. Additionally, for instructors who had direct experience with technology and witnessed its benefits in teaching, they were also more inclined to integrate it into their curriculum for pupils (Cox & Graham, 2009;Kim & Lee, 2022).…”
Section: Introductionmentioning
confidence: 86%
“…The surge in research during 2020 can be attributed to the COVID-19 pandemic outbreak, which disrupted students' educational activities. The pandemic compelled educational institutions to adopt blended learning in their teaching practices, leading to increased research efforts to understand [38], [39], [40], [43], [46], [47], [49], [53], [ The authors' affiliation countries shown in Table 2 and Figure 4 show that Indonesia has the highest number of publications (10 studies), published between 2019 and 2022. This can be explained by the requirement for practical standards when implementing Blended Learning in Mathematics Teacher Education: A Systematic Review social distancing starting in 2019 to stop the spread of COVID-19.…”
Section: Data Extractionmentioning
confidence: 99%
“…Mixed model [43], [46], [48], [49] Online practicing model [31], [32], [33], [38], [51], [55] 6 24.00…”
Section: Modelmentioning
confidence: 99%
“…Augemented Reality yang dikembangkan yang memiliki topik terkait Covid-19 tetapi cenderung lebih ke cara pembelajaran pada masa [3], [4], [5], [6], [7], [8], [9], [10], [11], [12] dan [13] bukan pengenalan akan penerapan new normal. Peneliti memberikan batasan dalam penelitian ini yaitu:…”
Section: Ada Beberapa Aplikasi Berbasisunclassified